Chronic sleep deprivation induces plasma exosome-derived miR-150-5p downregulation as a novel mechanism involved in Parkinson’s disease progression by targeting DCLK1 - Li Liu; Xiangting Liu; Runze Zhang; Xiao Sun; Keping Zhang; Beibei Zheng; Ruoxi Yang; Kaiyue Yang; Guohua Song; Zhaoqiang Zhang (Journal of Translational Medicine)
Abstract Background Researches have suggested that chronic sleep deprivation (SD) can lead to neurological dysfunction and facilitate the onset and progression of Parkinson’s disease (PD). However, the association between SD and PD remains unclear. Exosome (exo) cargo comprises microRNAs (miRNAs), which are potential regulators of PD. This study focused on assessing the role and related mechanisms of SD on PD. Methods SD plus 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mice were used to investigate effects of SD on PD. Exos were extracted from plasma by polymer precipitation method. Impacts of exos on PD were validated through intervention in 1-methyl-4-phenylpyridinium (MPP+)-induced PD cells and MPTP-induced PD mice. Levels of miRNA in exos were analyzed by gene expression profile microarray. Levels of miR-150-5p in exos and substantia nigra pars compacta (SNpc) were further confirmed by reverse transcription quantitative polymerase chain reaction (RT-qPCR). Target genes of miRNAs were predicted by TargetScan and confirmed by Dual-Luciferase Reporter Assay. Mimics and inhibitors of miR-150-5p were transfected into MPP+-induced PD cells, while agomir and antagomir of miR-150-5p were stereotaxic intracranial injected into SNpc of SD + MPTP-induced PD mice, enabling the determination of specific molecular mechanisms affecting PD. Results We found that SD and SD-derived exos aggravated PD-related damage. SD-derived exos were identified as potent inducers of PD. MiR-150-5p was recognized as a key element in SD-derived exos, and doublecortin-like kinase 1 (DCLK1) was confirmed as its target gene. Supplementing miR-150-5p alleviated PD damage by inhibiting DCLK1 and abnormal α-synuclein (α-syn) expression, decreasing reactive oxygen species (ROS), p62, cleaved-caspase-3 and cleaved-caspase-9 levels, and increasing Parkin and PINK1 levels and the LC3II/I ratio. Conclusion These findings suggested that miR-150-5p-dependent downregulation in SD-derived exos could aggravate the progression of PD via the DCLK1/α-syn pathway. MiR-150-5p decreased ROS levels, promoted mitophagy, and inhibited apoptosis, thus mitigating PD-related damage. These findings indicated that plasma-derived exos and their miRNA cargo might serve as therapeutic targets for PD, providing insights into a mechanism that links SD-related deterioration to the progression of PD.